Draft Outline Fifth Five Year Plan Assam Volume I - Planning Commission (Planning Commission, 1973)
The preparation of a Draft Outline for the Fifth Five Year Plan was entrusted to the State Planning Board of Assam. The Draft Outline as prepared by the. Board has been considered by the Government of Assam and accepted for presentation to the Planning Commission. The outline is presented in three volumes. Volume I contains the Outline Proper, Volume II contains the Sectoral Programmes and Volume III contains the Appendices showing the exercises and methodology on which the outline has been framed by the State Planning Board.
Planning and Development Department Government of Assam